Effect of head orthoses on skull deformities in positional plagiocephaly: Evaluation of a 3-dimensional approach. Issue 6 (June 2018) - Dörhage, Klaus W.W.; Wiltfang, Jörg; von Grabe, Vera; Sonntag, Annalena; Becker, Stephan T.; Beck-Broichsitter, Benedicta E.
Abstract: Purpose: The positional non-synostotic plagiocephaly represents a cranial asymmetry affecting all 3 dimensions. The aim of this study was to evaluate volumetric indices to assess the efficiency in improving non-synostotic cranial asymmetries in treatment with head orthoses. Material and methods: A total of 96 infants were included in this observational retrospective study. The cohort was further divided into subgroups according to age of helmet supply (younger/older than 7.5 months) and duration of therapy (less/more than 150 days). With 3-dimensional photogrammetry data sets, the skull volume was separated into quadrants and set in relation to each other to create an Anterior Cranial Asymmetry Index (ACAI) and a Posterior Cranial Asymmetry Index (PCAI) as 3-dimensional parameters. Results: Treatment with head orthoses led to a significant reduction of ACAI (p < 0.0001) and PCAI (p = 0.001). Cranial asymmetry was more severe in the occipital region and significantly improved mainly during the first 75 days with a 40.08% decrease of PCAI value in the short-term therapy in the younger treatment subgroup (p = 0.003). Conclusions: The introduced parameters sufficiently reproduce the improvement of asymmetry during helmet therapy, following the trend of already established parameters. Asymmetry was significantly improved in the occiput region, and helmet therapy was highly effective in younger infants and in the early treatment period.